PKM Sosialisasi Capaian Pembelajaran Pada Kurikulum Merdeka Di Sekolah Yayasan Kemala Bhayangkari Makassar - Ervi Novitasari; Muhammad Rais; Hartini Ramli; Khaidir Rahman; Andi Alamsyah (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The independent curriculum is a new policy first launched by the Minister of Education, Nadiem, which aims to hone children's interests and talents from an early age, by focusing on essential material, character development and student competencies. There are changes to the subject structure and the way the learning process is carried out in the Independent Curriculum. With these changes, the teaching staff at Kemala Bhayangkari Foundation schools still need guidance regarding the implementation of learning outcomes (CP) in the independent curriculum. To optimize curriculum implementation, the FT UNM Agricultural Technology Education PKM team carries out outreach and assistance to teaching staff. This activity aims to provide knowledge to teaching staff regarding the urgency and implications of the independent curriculum as well as the implementation of learning outcomes in the independent curriculum. Implementation of socialization is carried out using discussion and question and answer methods, where the socialization process carried out by teaching staff shows high interest and enthusiasm so that it has an impact on improving knowledge. This, supported by the questionnaire data that has been analyzed, shows that the category is very good (satisfactory) compared to the unsatisfactory category before the socialization was carried out.